Power Inequality in The Conflict Over The Burning of Chicken Farms in Padarincang From The Perspective of The Power Cube - Shezy Solevina Putri; Yeby Ma'asan Mayrudin (Journal of Political and Governance Studies, 2025)
Background This study aims to analyze the inequality of power relations in the conflict of burning chicken farms in Padarincang from the perspective of the power cube. The background of environmental problems due to chicken farming activities and advocacy that was not responded to by various government agencies created an accumulation of frustration that encouraged extreme acts of burning chicken farms. Methods This research uses John Gaventa's Power Cube theory and uses qualitative research methods with John Creswell's hermeneutic phenomenology approach. Results The results of the research found that the hierarchical structure of the corporation shows the connectedness of local to global actors. This conflict illustrates the transformation of closed spaces into open spaces through community struggles and various forms of power from visible power in the form of company licenses, arrests and demonstrations.   Conclusions Hidden power in the form of lobbying and chicken hotel narratives, the issue of arresting mothers, hoax news to invisible power in the form of internalization of the community over the developing narrative and ideology of economic development. The complex inequality of power relations between the community and PT STS creates marginalization, injustice, legal disparities that continue to envelop the community in fear.